The use of human‐derived feeder layers for the cultivation of transplantable human epidermal cell sheet to repair second degree burn wounds. Issue 2 (12th February 2023) - Mingqi, Zhang; Le, Wang; Yuqiang, Zheng; Na, Li; Wei, He; Zhuoshi, Wang
Abstract: Background and objectives: Human epidermal cell sheet (human‐ECS) is a feasible treatment option for wound injury. Traditionally, researchers often use murine 3T3 fibroblast cells as feeder layer to support human epidermal cell sheet grafts, thus increase risk to deliver animal‐borne infection. To overcome the potential risks involved with xenotransplantation, we develop human foreskin fibroblast cell as feeder layer culture system and investigate the effects of human‐ECS on second‐degree burn wound healing in mini‐pig in order to develop more effective and safer therapies to enhance wound healing in human. Materials and methods: Human epidermal keratinocytes and fibroblasts were isolated from foreskin tissue and were co‐cultured to manufacture human‐ECS. The cell morphology was monitored with phase‐contrast microscopy, the stem cell markers were assessed by flow cytometry, and by colony‐forming efficiency (CFE) assay. The structure of human‐ECS was observed by hematoxylin and eosin staining. Expression of cytokines in human‐ECS was confirmed by enzyme‐linked immunosorbent assay. Second‐degree burn wounds were created on the dorsal of miniature pig to evaluate the effect of oil gauze, oil gauze combined with commercial epidermal growth factor (EGF) cream, and oil gauze combined with human‐ECS. Wound healing rate, histological examination, and Masson staining were measured to observe the wound repair efficacy. Real‐time PCR and Western blot were utilized to detect the expression level of EGF and interleukin 6 (IL‐6). Results: Stratified human‐ECS with 6‐7 layers of epidermal cells was successfully cultivated with human‐derived feeder cells, in which epidermal cell highly expressed CD49f and CFE was 3% ± 0.45%. Application of human‐ECS induced a higher wound healing rate than commerical EGF cream and oil gauze control. The expression of EGF in human‐ECS group was higher than those in the other groups; however, the expression of IL‐6 was significantly decreased at day 14 by human‐ECS treatment group. Conclusions: Human‐derived feeder cells are suitable for cultivation of human‐ECS, avoiding pathogen transmission. Human‐ECS could enhance second‐degree burn wound healing, and its promoting effect involved secreting a variety of cytokines to regulate tissue reparative process.